Math Doubts

Sum of two Inverse sine functions


$\large \sin^{-1} x + \sin^{-1} y$ $\large \,=\,$ $\large \sin^{-1}[x\sqrt{1-y^2}+y\sqrt{1-x^2}]$


$\alpha$ and $\beta$ are two angles of the two right angled triangles and the compound of angle of them is $\alpha + \beta$. The sine of the sum of two angles can be expanded in terms of sine and cosine of both angles.

$\sin(\alpha+\beta)$ $\,=\,$ $\sin \alpha \cos \beta + \cos \alpha \sin \beta$

One the basis of this trigonometric formula, the sum of two arcsin functions can be expressed in mathematical form.


Transformation of sine functions

Take $\sin \alpha = x$ and $\sin \beta = y$.

$(1) \,\,\,\,\,\,$ $\sin \alpha = x \implies \alpha = \sin^{-1} x$

$(2) \,\,\,\,\,\,$ $\sin \beta = y \implies \beta = \sin^{-1} y$


Transformation of cosine functions

According to the Pythagorean identity of sine and cosine functions, express $\cos \alpha$ and $\cos \beta$ in square root form of $\sin \alpha$ and $\sin \beta$ respectively.

$\cos \alpha = \sqrt{1-\sin^2 \alpha} \,\,\,$ and $\,\,\, \cos \beta = \sqrt{1-\sin^2 \beta}$

As per our consideration, $\sin \alpha = x$ and $\sin \beta = y$. Now, transform the above two equations in terms of $x$ and $y$ purely.

$(3) \,\,\,\,\,\,$ $\cos \alpha = \sqrt{1-x^2}$

$(4) \,\,\,\,\,\,$ $\cos \beta = \sqrt{1-y^2}$


Transformation of sine of sum of angles

Transform the sine of sum of angles rule purely in terms of x and y to obtain the formula of sum of two inverse sine functions.

$\sin(\alpha+\beta) \,=\, \sin \alpha \cos \beta + \cos \alpha \sin \beta$

$\implies \sin(\alpha+\beta)$ $\,=\,$ $(x)(\sqrt{1-y^2})$ $\,+\,$ $(\sqrt{1-x^2})(y)$

$\implies \sin(\alpha+\beta)$ $\,=\,$ $(x)(\sqrt{1-y^2})$ $\,+\,$ $(y)(\sqrt{1-x^2})$

$\implies \sin(\alpha+\beta)$ $\,=\,$ $x\sqrt{1-y^2}$ $\,+\,$ $y\sqrt{1-x^2}$

Express sine function in its inverse form.

$\implies \alpha+\beta$ $\,=\,$ $\sin^{-1} [x\sqrt{1-y^2}$ $\,+\,$ $y\sqrt{1-x^2}]$

Replace, $\alpha$ and $\beta$ in terms of $x$ and $y$.

$\therefore \,\,\,\,\,\, \sin^{-1} x + \sin^{-1} y$ $\,=\,$ $\sin^{-1} [x\sqrt{1-y^2}$ $\,+\,$ $y\sqrt{1-x^2}]$

It is a property of the inverse trigonometry to write summation of two inverse sine functions in the form of same inverse sine function.

Math Questions

The math problems with solutions to learn how to solve a problem.

Learn solutions

Math Worksheets

The math worksheets with answers for your practice with examples.

Practice now

Math Videos

The math videos tutorials with visual graphics to learn every concept.

Watch now

Subscribe us

Get the latest math updates from the Math Doubts by subscribing us.

Learn more

Math Doubts

A free math education service for students to learn every math concept easily, for teachers to teach mathematics understandably and for mathematicians to share their maths researching projects.

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved